Nanostructured back reflectors for improved light absorption in silicon thin film solar cells - Li, Zeyu (2018)
The study on photovoltaic is an important topic in the sustainable and clean energy research field, driven by the deteriorating energy crisis and environmental pollutions due to fossil fuel shortage and combustion. Currently, crystalline silicon (c-Si) based solar cell dominates the photovoltaic market. However, its high material cost has weakened its competitiveness against fossil fuels. To reduce the material cost, silicon thin film based solar cell that uses less material is favourable. However, this will result in reduced optical absorption and consequently lower cell efficiency. To address the issue, nanostructures can be incorporated into the thin film solar cell for light trapping and to improve the optical absorption.